Characteristics and Agronomic Efficiency of Fertilizer Urea Granules- Acidic Coated Bamboo Biochar Acrylate on Plant Onion Red (Allium ascaloniucm L.) - I Kadek Ekadana; Dewa Ayu Ari Febriyanti (Journal of Sustainable Development Science, 2023)
The use of urea-biochar granular fertilizer is intended to overcome the problem of inefficiency in the excessive use of urea fertilizer. The efficiency of urea is relatively low because 40-70% of N is lost from the soil. The purpose of this study was to determine the agronomic efficiency of acrylic acid-coated bamboo urea-biochar fertilizer on shallot plants. The research was conducted in the greenhouse of UPT Plant Pest and Disease Control Center in Celuk Sukawati Gianyar Village, and in the Laboratory of Soil and Environmental Sciences, Faculty of Agriculture, Udayana University, arranged in a Completely Randomized Design with a single factor consisting of 9 treatments and repeated 3 times. Parameters observed were plant growth yields (height, weight of tubers and fresh litter, weight of tubers and oven-dried litter, number of tillers), fertilizer agronomic efficiency. The results showed that the S30 treatment significantly increased the shallot plant height by 43.67 cm, the weight of the oven-dried bulbs by19.68 g and the RAE value by 362%, so that fertilization with the S30 treatment was the most efficient compared to other treatments and could be used by farmers in increasing the growth and yield of shallot plants.